The development of prosocial behavior from late childhood to adolescence: a longitudinal and multicultural study - Cirimele, Flavia; Pastorelli, Concetta; Remondi, Chiara; Zuffianò, Antonio; Thartori, Eriona; Gerbino, Maria; Di Giunta, Laura; Bacchini, Dario; Oburu, Paul; Skinner, Ann T.; Sorbring, Emma; Steinberg, Laurence; et al. (Frontiers in Developmental Psychology, 2024)
Introduction Prosocial behavior (i.e., voluntary actions aimed at benefiting others, such as helping, comforting, and sharing) has proven beneficial for individuals' adjustment during the transition to adolescence. However, less is known about the role of the broader sociocultural context in shaping prosocial development across different cultures. Thus, the present study explored the longitudinal trajectory of prosocial behavior in the transition to adolescence (from ages 9 to 16) by examining the role of the Human Development Index (HDI) in relation to prosocial development. Methods A sample of 915 children (Time 1: 50.5% males; Mage = 9.24, SD = 0.69) across six countries (Colombia, Jordan, Italy, the Philippines, Thailand, and the United States) participated in the study. Over four time points covering 7 years, prosocial behavior was assessed using a self-report measure. Results A second-order Latent Growth Curve Model, controlling for child gender and family SES, showed that prosocial behavior remained stable in contexts with high HDI, whereas increases in prosocial behavior were evidenced as children moved into adolescence in contexts with low HDI. Moreover, cultural differences in the mean level of prosocial behavior were shown during late childhood and the earliest phase of adolescence, whereas the national development of a given context did not account for differences in prosocial behavior during late adolescence. Discussion Findings underscore that national life expectancy, education, and wealth play a role in age-related changes in other-oriented behaviors during adolescence. The role of sociocultural factors in shaping trajectories of prosocial behavior across six countries is discussed.